A comparative review of self-rotating and stationary twisted tape inserts in heat exchanger. (January 2016) - Zhang, Cancan; Wang, Dingbiao; Ren, Kun; Han, Yong; Zhu, Youjian; Peng, Xu; Deng, Jing; Zhang, Xiying
Abstract: Heat transfer enhancement techniques are popularly used in various engineering applications such as heat exchanger, air conditioning, chemical reactors and refrigeration systems. Twisted tape is one of the most important passive techniques, which has been proved to disturb the flow fluid in tube and then strengthen the heat transfer efficiency. This paper conducted comprehensive and comparative review on experimental and numerical works taken by researchers on self-rotating and stationary twisted tapes. It is found that the heat transfer enhancement and the function of online anti-scaling and descaling in tube can be obtained with the self-rotating twisted tapes. Meanwhile, the tube with self-rotating twisted tapes gives the lower pressure drop. Both heat transfer coefficient and friction factor increase with the decreasing of twisted ratio. The twisted tapes combined with different modified techniques are the new development directions of heat transfer enhancement. The appropriate twisted tape modification is necessary for heat transfer enhancement with pressure loss penalty at a reasonable level.